(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to identify the most important psychological and behavioral problems resulting from the excessive use of electronic games by children the descriptive method was used as it was appropriate for the nature of this study during the academic year 2025_2026 Based on the theoretical framework and previous studies several recommendations were reached these include strengthening the role of the family and parents in raising awareness about the risks of electronic games as well as monitoring the types of games children participate in to ensure they are appropriate for their ages the study also recommends limiting children’s gaming time so that it does not exceed one hour per day in addition to encouraging local production of purposeful educational games .